Parents Experience in Giving Sex Education to Adolescents in North Kuta - Sanjiwani, Ida Arimurti; Pramitaresthi, I Gusti Ayu (Journal of A Sustainable Global South; Vol 5 No 2 (2021): August 2021, 2021)
Sexual education is an important think that parents can do to prevent free sex and it effects in adolescent. It is possible because family is the first place of education, but it appears to be inadequately practiced in Indonesia. This study aims to determine parent experience to provide sexual education in adolescents. We used a phenomenology interpretative approach in this study. We collected the data through in-depth interviews with ten parents. We found five themes: (1) good perception about sexual education, (2) sexual education delivered assisted by social media, (3) the topic is free sex, (4) difficult to start because of taboo and shame, (5) need support from health worker. The study reveals that sexual education is limited and need to be increased. It is essential that Indonesian parents become better informed and skilled, so that they may be involved in the sexual education of adolescent start from their family. Index Terms — sexual education, adolescent, parents experience